Business Models and Selected Performance Metrics of Philippine Airlines and Cebu Pacific - Doria, Sheena; De Vera, Jr., Leo; Parel, Danice Angelee (Southeast Asian Journal of Science and Technology, 2017)
Philippine Airlines (PAL) and Cebu Pacific serve as the market leaders and the strongest competitors in the Philippine airline industry. The paper focused on determining the similarities and differences in the business models of PAL and Cebu Pacific representing full-service carriers (FSC) and low-cost carriers (LCC), respectively. The study evaluated and compared eighteen factors of the airline business model and selected performance metrics of PAL and Cebu Pacific. The two airlines differ in all the factors evaluated as they more or less in accordance with their original business models. However, PAL and Cebu Pacific have slightly adapted from each other’s business models at some extent. Results showed that Cebu Pacific tends to deviate 77.78% from its original model. PAL, on the other side, had 94.44% conformity with its original model. From the results, “hybridization” that is used by LCCs is also manifested by FSCs and vice versa as shown in the cases of PAL and Cebu Pacific. It was seen that Cebu Pacific performed better than PAL in terms of profits, load factors, costs, and labor productivity from 2009-2013. Although both the airlines had modifications in their respective models especially in 2013, the sustainability of their decisions models will be manifested in the long run.